TEMBANG (LAGU) DOLANAN ANAK SEBAGAI INSPIRASI PENCIPTAAN TARIAN ANAK - Untung Muljono (SELONDING, 2017)
Tembang Dolanan Anak is a creation (fruit of thought) or the composition of the language with the rules of the standard (gumathok) which way of reading it must be dilagukan by using the beauty of sound owned. Tembang (sekar) Java is divided into two categories, namely classic and folk type. The classical tembang is a tembang whose source is from the Javanese royal court from the time of Kediri to Mataram Islam (Yogyakarta and Surakarta), therefore the rules are very strict. The song that developed in the people's circle (in the Hindu era belongs to the caste of waisya and sudra) the mention is "song, lagon, or lelagon" there is no binding rule (free) only certain songs. Types of Dolanan Tembang Anak many developed in society that tell about behavior pattern and character owned by children. Therefore Tembang Dolanan Anak has a noble value education on the meaning contained in it. It inspires children's dance making. The method used in applying in the form of child dance that is with the approach of phenomenology with emphasis on the strength of creative ideas creation by Edmund Huserr. Phenomenology in his view does not make the object a fact but rather abstracts the objects.The results obtained by looking at the source of inspiration from Tembang Dolanan Anak make the child dance more meaningful in the forms of movement that was created. The choreography created can be tailored to the child's character and behavioral patterns.